INTEGRATION OF ACTIVE LEARNING METHODOLOGIES IN THE TEACHING OF MAXILLOFACIAL PATHOLOGY: EXPERIENCE REPORT AND CRITICAL ANALYSIS - Fulco Júnior, Marco Antônio; Honorio, Daniel José da Silva; Martins, Laura Rocha; Sena, Ana Júlia Fortes; Araújo, Savio Abreu de; Paula, Lorrayne Naysla de; Fabri, Júlia Campos; Roeles, Iasminy Soares de Oliveira; Fabri, Gisele Maria Campos (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2026)
This study aims to descriptively and reflectively report the experiences of undergraduate dental students who participated in active learning methodologies in the Maxillofacial Pathology II and III courses. This observational study explored the implementation of case-based, team-based, problem-based, and project-based learning strategies. These methodologies were employed throughout the academic semester and incorporated into the courses’ assessment criteria. The integration of active learning methodologies served as a pedagogical strategy to facilitate students’ knowledge construction. These approaches made learning more meaningful and enhanced information retention, while also promoting a more engaging, dynamic, and collaborative learning environment by valuing teamwork. However, successful implementation requires faculty training in active methodologies and active student engagement to achieve optimal learning outcomes. In conclusion, active learning methodologies proved to be effective instructional strategies, as they contributed to the development of essential competencies for the students’ professional education.